Supply chain temple of resilience - Wilding, Richard D. (Charlton Grant, 2016)
In March 2011, an earthquake and tsunami hit the north-eastern coastline of Japan. Honda, Toyota, Nissan and Subaru all had plants in or close to the affected region, and were forced to close them.